Bioluminescence imaging of dual gene expression at the single-cell level - HyuckJoon Kwon; Toshiteru Enomoto; Masahiro Shimogawara; Kazunori Yasuda; Yoshihiro Nakajima; Yoshihiro Ohmiya (BioTechniques)
Bioluminescence imaging reveals the long-term dynamics of individual gene expression in a single cell. However, methods for simultaneously imaging multiple gene expression patterns have been unknown to date. Here, we constructed a dual-path optical luminescence imaging system using a two-color reporter system and could simultaneously track two gene expression patterns for several days in a single cell.